Impact of HIV-1 tropism on the emergence of non-AIDS events in HIV-infected patients receiving fully suppressive antiretroviral therapy - Maffongelli, Gaetano (AIDS, 2016)
OBJECTIVE: The impact of HIV-1 tropism on the emergence of non-AIDS events was evaluated in a cohort of 116 antiretroviral therapy (ART) responder patients. METHODS: The patients were followed for the emergence of hypertension, renal impairment, metabolic and bone disorders (defined as non-AIDS events) each 8 weeks at standard visits. A V3 plasma sequence genotype analysis was performed at the time of ART initiation and the geno2pheno algorithm with the results that defines the false-positive rate (FPR) was used to infer HIV tropism. The associations between the non-AIDS events and the FPR at baseline were evaluated using the χ(2) test for trend. A Cox-regression analysis using the counting process formulation of Andersen and Gill was performed to define whether the emergence of non-AIDS events was correlated to FPR. RESULTS: The prevalence of at least one non-AIDS event resulted higher in patients with a FPR below 10% than in patients with a R5 virus (P = 0.033). Patients with a FPR below 5.0% most frequently developed non-AIDS events during ART (P = 0.01). A higher prevalence of patients with at least two AIDS events was found in the group of patients with a FPR below 5.0% with respect to the others (P < 0.001). At multivariate Cox-regression analysis, having an X4 virus and age were independently associated with a higher probability of non-AIDS event development. CONCLUSION: This study shows that an X4 virus, particularly a FPR less than 5%, is related to non-AIDS events development. Further studies are warranted to understand the mechanisms underlying this phenomenon.